Social Marketing - Predicting the Impact of Government Aided Health Insurance Project in Rural Tamil Nadu - Swaminathan, T. N.; Viswanathan, P. K. (Indian Journal of Marketing, 2016)
Social marketing is using marketing principles to influence the acceptability of social ideas. In developing countries, one of the contexts of social marketing is using marketing principles to foster the use of various health-related products and services independent of non-governmental organizations (NGOs) and donors through local organizations - state owned, state supported, and private . In India, there is a growing demand for quality medical care due to poor quality of state owned hospitals, increase in lifestyle diseases, increasing private healthcare costs, and cost of medicines. This makes health insurance a necessity today more than a luxury. To mitigate the problem of quality health care at affordable costs, there are state interventions, the notable ones being Yeshasvini of Karnataka, Arogyasri of Andhra Pradesh, & â€œChief Minister Insurance Scheme for life saving treatmentsâ€ of Tamil Nadu. â€œChief Minister Insurance Scheme for life saving treatmentsâ€ in Tamil Nadu is one of the innovative health insurance schemes introduced by Tamil Nadu Government in 2009 for below poverty line (BPL) families covering a population of 14 million with an annual income of INR 72000 (USD 1400 ; 1 USD = 50 INR in 2009) or less. The scheme was implemented through 663 hospitals (20 public sector hospitals and 643 private hospitals). This scheme assures treatment and saves peoples' lives from 51 types of diseases. This study is the second part of a study that is aimed at studying the public - private partnership in health care with specific reference to the â€œChief Minister Insurance Scheme for life saving treatmentsâ€ scheme of Tamil Nadu, India. While the first part looked at awareness and satisfaction, the present study focused on its impact through qualitative and quantitative research methodologies. The study indicated the impact that the scheme has created in the lives of the people is significant. People who cannot afford treatment from the private hospitals are now highly dependent on this scheme for their health care needs.